Pengaruh Gaya Kepemimpinan, Knowledge Management dan Budaya Organisasi terhadap Kinerja Karyawan - Bintang Alhakim; Suhana (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to assess the influence of leadership style, knowledge management, and organizational culture on employee performance. The research was conducted at PT. ARISA MANDIRI PRATAMA using employees from the production division as samples. Convenience sampling was the method used to select samples. Data validity testing utilized factor analysis. Data analysis was performed using SPSS version 27.0 software. The research results indicate that leadership style significantly affects employee performance. Additionally, knowledge management also plays a role in influencing employee performance, while organizational culture does not have a significant impact on employee performance. This study contributes both theoretically and practically.